EDUKASI PENDIDIKAN AGAMA ISLAM UNTUKHUMAN LIFE: BUDAYA MEMBACA SURAT AL-WAQIAH DAN PEMAHAMANNYA DI MTS THOYIB HASYIM JORONGAN PROBOLINGGO - Rodiyatul Maula; Ulil Hidayah (LPPM STAI Muhammadiyah Probolinggo, 2024)
Islamic religious education has a foundation from the Koran and Hadith as education. The aim of Islamic education is to create Muslim successors with good moral character. At this time, various verses explain how important it is to study the Koran, at least read it, see the decline in morals. Reading and studying the Koran is an obligation for every Muslim. The surah in the Qur'an that is widely practiced or often read by many people is surhAl-Waqiah with various believed meanings. This research uses a qualitative approach, which takes place scientifically. The methods for collecting data are observation, interviews and documentation.